FT-IR detection of organic and biogenic components in the soils from archaeological site Novgotod-Siversky - Pykhova, O. V.; Kuchmenko, O. V. (Biophysical Bulletin, 2021)
Background: Biophysical research methods as a powerful tool for studying small quantities of samples, are successfully used in related fields — forensic medicine, agriculture, archeology. The use of infrared spectroscopy is a progressive method due to the possibility of non-destructive analysis, easy sample preparation and high sensitivity, allowing to supplement historical reconstruction. It is possible to identify individual organic molecules by infrared spectroscopy. It is important to study the soil from the excavation site because all the anthropogenic processes that took place in the appropriate place are reflected in the composition of the soil. Objectives: Discover of organic remains in the soil from the object of archeological site and to identify organic molecules. Materials and methods: The object of research is the soil from 3 different objects (2 buildings and a ditch), which were identified within one excavation, Novgorod-Siversky, Chernihiv region. According to preliminary data, the objects are ancient Russian. For the study, 3 incremental samples were collected from each object. Further, the physicochemical properties of the selected soil were studied and spectroscopic studies were performed to determine the presence of low- and high-molecular compounds in the material. Results: It was determined that the pH level of the test samples ranges from weakly acidic to alkaline. The pH of the parent breed is slightly alkaline. FT-IR spectroscopy revealed DNA molecules, proteins, and lipids at the second site in soil samples from sites 1 and 2 (buildings). Only proteins are present in the ditch (№3). Instead, only mineral components were observed in the parent rock. Microscopy of soil samples revealed that the grains of sand from the ditch (№3) have a rounded shape, which is typical for places that have been in prolonged contact with water. Also, microscopy revealed traces of charcoal from the second site. Conclusions: The presence of organic components in the studied soils may be the result of human habitation and long-term activity. The presence of charcoal residues and identified lipid molecules in the №2 samples may indicate that this site was associated with cooking. In this case, the soil from place № 3 (ditch) is depleted of organic residues and sand grains, which have a rounded shape, may indicate that this place has been in contact with water for a long time.